Life quality and health of children and youth of Ukraine - Павлова Юлія Олександрівна, (Iuliia Pavlova) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: to describe the parameters of schoolchildren’s life quality. Material and Methods: the studies were conducted during 2012–2014 in L’viv region (Ukraine). 988 schoolchildren at the age of 15–16 years, 300 – at the age of 13–14 years, 406 – at the age of 11–12 years were surveyed with PedsQL questionnaire. Results: it was shown the respondents positively characterized the physical and social health, but their mental state was unsatisfactory. The amounts of children who had serious difficulties with basic physical activity and problems with social communication did not exceed 7%. Conclusions: the average life quality indicators were in the range 71,9–85,0 points and according scales Physical Health, Emotional Functioning, School Functioning significantly reduced with age.